Large acrochordon of labium majora: an unusual location - Citrashanty, Irmadita; Luthfidyaningrum, Hamidah; Murtiastutik, Dwi; Hidayati, Afif Nurul; Widyantari, Septiana; Astindari, Astindari; Sari, Maylita (Explorer Front, 2023)
Background: Acrochordon is a soft, round or oval, pedunculated papilloma that can be tan or brown in color. Although acrochordons most commonly appear in the neck, axilla, and groin, they can also appear in unusual sites, such as penis, vulva, and perineum. Most of the lesions are small pedunculated papules or nodules approximately 2–6 mm, but rarely, particularly on the lower section of the trunk, large pedunculated acrochordons can be found. Here we present a large acrochordon on the labium majora. Case Description: A 25 years old woman came to an outpatient clinic because there was a mass on her right labium majora ever since she gave birth three years prior. The size of the mass started off relatively small but has grown significantly over time. From dermatological examination in external genitalia region, there was a solitary, pedunculated, skin-colored mass measuring 10 × 3 cm, attached to right labium majora. There was no redness, ulceration, bleeding or discharge. Cautery excision with local anesthetic was performed to removed the mass. The histopathological examination of the specimen revealed polypoidal tissue lined by epidermal layer, there are proliferation and dilation of capillaries containing erythrocytes in the dermis layer, mild infiltration of lymphocytes and histiocytes. No evidence of malignancy. Conclusion: We report an unusual location of acrochordon presenting with large size. Due to its atypical presentation, it may be confused with a malignancy, necessitating a pathological test. Total excision of the mass is recommended.